Naked short selling: The emperor`s new clothes? - Pradeep K. Yadav; Veljko Fotak; Vikas Raman (University of Cologne, Centre for Financial Research (CFR), 2009)
Regulatory and media concern has focused heavily on the potentially manipulative distortion of market prices associated with naked short selling. However, naked shorting can also have beneficial effects for liquidity and pricing efficiency. We empirically investigate the impact of naked short-selling on market quality, and find that naked shorting leads to significant reduction in positive pricing errors, the volatility of stock price returns, bid-ask spreads, and pricing error volatility. We study naked shorting surrounding the demise of financial institutions hardest hit by the financial crisis in 2008 and find no evidence that stock price declines were caused by naked shorting. We also find that naked short-selling intensifies after rather than before credit downgrade announcements during the 2008 financial crisis. In general, we find that naked short sellers respond to public news and intensify their activity after price declines rather than triggering these price declines. We study the impact of the SEC ban on naked short selling of financial securities during July and August 2008, and find that the ban did not slow the price decline of those securities and had a negative impact on liquidity and pricing efficiency. Finally, after examining the speeds of mean reversion of pricing errors and order imbalances, we infer that Regulation SHO was successful in curbing the impact of manipulative naked short selling, and this reduction in the impact of manipulative naked shorting has continued through the 2008 financial crisis. Overall, our empirical results are in sharp contrast with the extremely negative preconceptions that appear to exist among media commentators and market regulators in relation to naked shortselling.
Keywords: G10; G14; G18; 330; Naked Short Selling; Short Selling; Pricing Efficiency; Leerverkauf; Wertpapierhandel; Marktliquidität; Börsenkurs; Markteffizienz; Regulierung; Wirkungsanalyse; USA